Small Round Blue Cell Tumor Retinoblastoma vs. Neuroblastoma - Sohail, Aliena; Naseem, Lubna; Imtiaz, Amna (International Journal of Pathology, 2018)
In histopathology, a small blue cell tumor or small round blue cell tumors refer to tumors comprised of “blue”cell with very scant cytoplasm. As nucleus stains blue and cytoplasm pink, these tumors impart a distinct”blue”appearance”. These cells at low magnification resemble mature lymphocytes which also posses scant cytoplasm.However are significantly larger than small lymphocytes and erythrocytes. Leukemia, lymphoma, poorlydifferentiated carcinomas like oat cells carcinoma and several other primitive tumors may give this picture onhistology sections. These tumors can be seen in any age group. 1&2 Here we report a four month old female childwith diagnosed primary lesion of neuroblastoma in the right eye (from an outside laboratory) followed bymetastasis to the bone marrow within a period of three months. This was a very rare finding because only 3 caseshad been previously reported of Primary Neuroblastoma in the eye and that too with no metastasis. Thecommonest eye tumor in this age group is of course retinoblastoma which can alo spresent congenitally as well aswith metastasis. Immunohistochemistry of both Neuroblastoma and Retinoblastoma give same positivity to thesame markers. Hence it is difficult to differentiate the two.